2000
DOI: 10.1179/026708300101508702
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of high performance lightweight steels

Abstract: The incorporation of low density, high modulus ceramic particles into a steel matrix is a potential route to improve the mechanical performance of steels. A powder metallurgy, mechanical blending route has been adopted to produce a homogeneous distribution of TiB 2 particles in both pure Fe and 316L stainless steel matrices. This approach gave large increases in both the static and fatigue strength with increasing TiB 2 volume fractions, in comparison with the matrix material. Additions of TiB 2 also resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…gears and drive-train parts), where intrinsically high stiffness and strength are necessary. Iron/steels offer the highest Young's modules of common engineering alloys (ϳ210 GPa), with recent work on PMMCs of iron-and steel-based matrices containing particulate titanium diboride (TiB 2 ) showing that materials may be produced with Young's moduli of up to 285 GPa for a reinforcement content of 30 pct, [2,3,4] while reductions in density are of course also realized by the addition of the reinforcement phase. While failure characteristics are often identified as a limiting factor in the use of structural PMMCs, it has been shown that mechanically alloyed particulate TiB 2 /iron-based composites that exhibit clear improvements in strength and stiffness over monolithic material may retain reasonable ductility, notched tensile strength, and fracture toughness levels.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…gears and drive-train parts), where intrinsically high stiffness and strength are necessary. Iron/steels offer the highest Young's modules of common engineering alloys (ϳ210 GPa), with recent work on PMMCs of iron-and steel-based matrices containing particulate titanium diboride (TiB 2 ) showing that materials may be produced with Young's moduli of up to 285 GPa for a reinforcement content of 30 pct, [2,3,4] while reductions in density are of course also realized by the addition of the reinforcement phase. While failure characteristics are often identified as a limiting factor in the use of structural PMMCs, it has been shown that mechanically alloyed particulate TiB 2 /iron-based composites that exhibit clear improvements in strength and stiffness over monolithic material may retain reasonable ductility, notched tensile strength, and fracture toughness levels.…”
Section: Introductionmentioning
confidence: 99%
“…While failure characteristics are often identified as a limiting factor in the use of structural PMMCs, it has been shown that mechanically alloyed particulate TiB 2 /iron-based composites that exhibit clear improvements in strength and stiffness over monolithic material may retain reasonable ductility, notched tensile strength, and fracture toughness levels. [3] As a number of promising potential applications of such composites are in aerospace and automotive components subjected to severe cyclic loads, the fatigue properties are clearly of interest. Fatigue strengths have been reported previously and shown to be superior to equivalent unreinforced materials; [3] however, details of the micromechanisms of failure and the associated implications for crack propagation resistance have not as yet been published.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, quite naturally, any strategy for reducing the density of steels must use components with densities lower than those of steels. The published literature points to the following broad strategies for density reduction of steels: Fe-based bulk (monolithic) alloys, 4 ferrous composites, [6][7][8][9] steel foams, 10,11 and steelbased laminates. 12,13 Although this overview on low-density steels deals mainly with the Fe-based bulk alloys, an introduction to each of the other concepts of achieving lower density in steels is included in the beginning.…”
Section: Introductionmentioning
confidence: 99%